Preparation and flexural property of composite of carbon black reinforced epoxy resin - Kesangam, Nattapon; Thammawichai, Warut (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2022)
Composite materials derived from epoxy resin that is thermoplastic are widely used in the 20th century due to their variety and flexibility in applications. It is commonly used in combination with carbon reinforcing to create a new kind of high-strength but lightweight material. The main objective of this research is to study and analyze the preparation of carbon black particles by a couple of ultrasonic technique, which is particle dispersion by ultrasonicate bath and ultrasonicate probe in 5 solutions: DI water, acetone, ethanol, methanol, and methyl ethyl ketone. And to study the flexural property of composite reinforced carbon black by the universal testing machine. As a result, it was found that the carbon black can be dispersed in 4 solutions: acetone, ethanol, methanol, and methyl ethyl ketone. However, it was precipitated after 60 minutes unless the carbon black was in the methanol solution. The particle in the methanol solution did not aggregate or precipitate to the bottom of the container after 5 days, which had an average particle size of 298.2 nm. In addition, composite materials reinforced 0.1, 0.2, 0.3, 0.4, and 0.5 wt.% of carbon black increase the flexural properties especially the stress at the yield point. The composite materials reinforced with 0.3 wt.% of carbon black increase the yield stress by 19% while Young’s modulus remains the same.